2010
DOI: 10.1016/j.yqres.2009.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and Climatic Changes in Deserts of China since the Late Pleistocene

Abstract: Large areas in western China were wetlands or less arid between 40 and 30 ka, corresponding to the "Greatest Lake Period" on the adjacent Tibetan Plateau. During the last glacial maximum, some of these western Chinese deserts again experienced wetter conditions; however, at the same time the sandy lands in the eastern Chinese desert belt experienced an activation of aeolian dunes. While interpretations of the midHolocene environment in the deserts of China are controversial, it is quite likely that it was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 61 publications
4
72
0
2
Order By: Relevance
“…Our stud ies of this al pine wet land suggests that there were more large flu vial dis charge events dur ing mid-Ho lo cene than dur ing the late Ho lo cene. These re sults were con sis tent with pre vi ous stud ies (Berg and Loutre, 1991;Wu et al, 2007) and suc cess fully ex plain the in flu ence of the Indian sum mer mon soon dur ing the early Ho lo cene and of the SE Asian sum mer mon soon and the wes ter lies dur ing the mid-Holo cene in the cen tre of the QTP (e.g., An et al, 2000;Fleitmann et al, 2003;Wang et al, 2005;Herzschuh, 2006;Chen et al, 2008;Yang and Scuderi, 2010).…”
supporting
confidence: 82%
“…Our stud ies of this al pine wet land suggests that there were more large flu vial dis charge events dur ing mid-Ho lo cene than dur ing the late Ho lo cene. These re sults were con sis tent with pre vi ous stud ies (Berg and Loutre, 1991;Wu et al, 2007) and suc cess fully ex plain the in flu ence of the Indian sum mer mon soon dur ing the early Ho lo cene and of the SE Asian sum mer mon soon and the wes ter lies dur ing the mid-Holo cene in the cen tre of the QTP (e.g., An et al, 2000;Fleitmann et al, 2003;Wang et al, 2005;Herzschuh, 2006;Chen et al, 2008;Yang and Scuderi, 2010).…”
supporting
confidence: 82%
“…it is a key region for understanding past climatic change and environmental evolution studies because it is located in the transition zone between the Asian summer monsoon and the westerly winds in China (Wang et al, 2005;Yang et al, 2011;Li et al, 2015). Thus, it is an ideal region for studying changes in climate at different time scales (Yang and Scuderi, 2010;Li et al, 2016c;Wang et al, 2016). however, for lakes in the hinterland of deserts, which are not recharged by river runoff, sediment is only transported by the wind (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Field investigations have shown that there have been clear climatic fluctuations accompanied by landscape changes and paleohydrological variations in the desert areas of western China during the Late Quaternary (e.g. Chen and Bowler, 1986;Thompson et al, 1989;Fang, 1991;Li and Shi, 1992;Owen et al, 1997;Lehmkuhl and Haselein, 2000;Zhang et al, 2000;Ye and Ji, 2001;Yang et al, 2003Yang et al, , 2011aYang and Scuderi, 2010), and in these areas presently under formation of sand dunes and desert plains, underlying relict gorges and alluvial fans are attributed to the local glacial maximum (Yang, 2001;Yang et al, 2004). Based on the gemorphological and sediment properties of the regional comparability, especially the low degree of weathering (Zhu and Yang, 2009), it is reasonable to attribute the relic forms of desert gorges and pediments in the margin of the Ejina Basin to the local glacial maximum of the last glaciation (LGM).…”
Section: Evidences From Pediments and Desert Gorgesmentioning
confidence: 99%
“…Northern China in Central Asia exhibits distinct variations in climate and hydrology during late Quaternary resulting in variation in the form and size of landscapes (Yang et al, 2010(Yang et al, , 2011a. Due to the absence of long and continuous sedimentary sequences in desert area, finding effective substitute in the deserts of world to understanding the Quaternary climatic history is still a difficult issue (Yang 2001;Yang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%